2006
DOI: 10.1089/thy.2006.16.73
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function in Humans with Morbid Obesity

Abstract: Morbidly obese subjects may present with abnormal thyroid function tests but the reported data are scarce. Therefore, we studied the thyroid parameters in 144 morbidly obese patients, 110 females and 34 males, to assess the prevalence of hypothyroidism. Eleven percent (11.8%) carried the diagnosis of hypothyroidism and were undergoing levothyroxine (LT4) replacement therapy, 7.7% had newly diagnosed subclinical hypothyroidism, 0.7% had subclinical hyperthyroidism and 7.7% were euthyroid with positive antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
224
6
16

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(275 citation statements)
references
References 35 publications
29
224
6
16
Order By: Relevance
“…In a large population study conducted in euthyroid patients from Denmark, 3 the body mass index (BMI) was found to be positively associated with serum TSH and inversely related to free tetraiodotyronine (FT 4 ). This finding has been confirmed in other studies, [4][5][6] but not in all. 7 However, in the latter report, study participants were referrals to a thyroid clinic.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…In a large population study conducted in euthyroid patients from Denmark, 3 the body mass index (BMI) was found to be positively associated with serum TSH and inversely related to free tetraiodotyronine (FT 4 ). This finding has been confirmed in other studies, [4][5][6] but not in all. 7 However, in the latter report, study participants were referrals to a thyroid clinic.…”
Section: Introductionsupporting
confidence: 76%
“…Furthermore, some studies were carried out in overweight individuals, others included morbidly obese individuals. 5 More recent studies have confirmed that diurnal serum TSH levels are significantly increased, if still within the normal range, in obese individuals, and that major weight loss induces a sizeable reduction in TSH and thyroid hormone levels. [8][9][10] It is unknown whether TSH has a role in favoring fat deposition or, on the contrary, whether excessive accumulation of adipose tissue increases TSH secretion.…”
Section: Introductionmentioning
confidence: 93%
“…Interestingly, the BMI of patients with subclinical hypothyroidism was significantly higher than euthyroid patients. The serum levels of TSH were higher in obese patients in some studies [37][38][39][40][41] but not in others [42,43]. The reason is still unclear because the BMI of patients with overt hypothyroidism was not different from the others also in our study.…”
Section: Discussioncontrasting
confidence: 62%
“…The minimum reference value of TSH ranged from 0.17 to 0.5 mU/l, whereas the maximum reference value of TSH ranged from 3.5 to 5.5 mU/l. Anthropometric measures used in the studies included BMI (4-6, 9-30), body weight (15,31,32), waist circumference (9,14,15,23,29,33), waist-hip ratio (9,15), hip (23), body fat percentage (13,15,17,21,23,29,32), subcutaneous (9,15,21,27) and central (21) fat, and fat mass index (fat mass (kg)/height (m)…”
Section: Resultsmentioning
confidence: 99%